What Caused the Extreme Indian Ocean Dipole Event in 2019? - Lu, Bo; Ren, Hong‐Li (Geophysical research letters, 2020)
An extreme positive Indian Ocean Dipole (IOD) event occurred in 2019 boreal autumn, which has induced severe climate impacts around the Indian Ocean basin. In this study, the cause for 2019 IOD event and the related mechanism are explored. We find that the remarkable strengthening of Australian high and weakening of sea level pressure over South China Sea/Philippine Sea have been evidently visible since May 2019. Such a record‐breaking interhemispheric pressure gradient (IHPG) induced northward cross‐equatorial flow over the western Maritime Continent, which triggered strong wind‐evaporation‐SST and thermocline feedbacks in 2019. In addition to 2019 case, historical IOD events are highly correlated with IHPG from boreal late spring to summer. We show that skillful IHPG prediction can be made in March by European Centre for Medium‐Range Weather Forecasts seasonal forecast system, which makes it quite possible for the early warning of extreme IOD events by two to three seasons ahead. Plain Language Summary During 2019 fall, an extreme Indian Ocean Dipole (IOD) event occurred. In this paper, the possible cause and mechanism of this event are investigated. We find that Australian high was strengthened, and Philippine Sea Anticyclone was weakened since May 2019. This interhemispheric sea level pressure gradient (IHPG) anomaly generates the northward cross equator over the Maritime Continent, which is crucial for the IOD growth. Not only for 2019 IOD, IHPG is a good indicator for almost all the IOD events in history. Since IHPG is predictable in March, the early warning of IOD events and resultant climate disasters could be possible. Key Points An extreme positive Indian Ocean Dipole (IOD) event occurred in 2019 The interhemispheric sea level pressure gradient (IHPG) across the Maritime Continent is suggested to be the cause of this IOD event The skillful prediction of IHPG could give rise to the successful IOD prediction by two to three seasons ahead